2014
DOI: 10.12966/abc.08.01.2014
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responding by Rhesus Monkeys (Macaca mulatta) and Humans (Homo sapiens) to Variable Outcomes in the Assurance Game

Abstract: . (2014). Differential responding by rhesus ronkeys (Macaca mulatta) and humans (Homo sapiens) to variable outcomes in the assurance game. Animal Behavior and Cognition, 1(3), 215-229. doi: 10.12966/abc.08.01.2014 Abstract -Behavioral flexibility in how one responds to variable partner play can be examined using economic coordination games in which subjects play against a variety of partners and therefore may need to alter their behavior to produce the highest payoff. But how do we study this behavioral fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 46 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…We did not have a prediction for the rhesus monkeys. Our work with the assurance game indicated that they found the payoff dominant Nash equilibrium with a simple propensity to choose the more valuable Stag option (Parrish et al 2014), but this would be unstable and inefficient whether they both played Fight or Yield in our game of conflict. Other work, however, shows that rhesus outperform capuchins on at least some complex cognitive tasks that require them to monitor outcomes (e.g., metacognition tasks: Beran and Smith 2011;Beran et al 2009), leaving open the possibility that they would be able to settle on at least one efficient Nash equilibria using a mechanism that wasn't apparent in the previous work.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…We did not have a prediction for the rhesus monkeys. Our work with the assurance game indicated that they found the payoff dominant Nash equilibrium with a simple propensity to choose the more valuable Stag option (Parrish et al 2014), but this would be unstable and inefficient whether they both played Fight or Yield in our game of conflict. Other work, however, shows that rhesus outperform capuchins on at least some complex cognitive tasks that require them to monitor outcomes (e.g., metacognition tasks: Beran and Smith 2011;Beran et al 2009), leaving open the possibility that they would be able to settle on at least one efficient Nash equilibria using a mechanism that wasn't apparent in the previous work.…”
Section: Introductionmentioning
confidence: 85%
“…A follow-up study in which subjects played a computer simulated partner demonstrated that humans and rhesus used different mechanisms. Rhesus showed a consistent propensity to play Stag across all patterns of random play (0%, 25%, 50%, 75%, and 100% Stag) whereas humans matched the frequency with which the simulation played Stag (Parrish et al 2014). Thus, the evidence indicates that rhesus were selected to be able to coordinate, but using a different, and presumably simpler, mechanism than is seen in humans.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Rhesus monkeys, chimpanzees, and humans, however, were still able to reach the payoff‐dominant NE when presented with the simultaneous AG. For humans and chimpanzees there is evidence that they understood a specific strategy (Brosnan et al, ), although for rhesus monkeys our evidence indicates that they simply developed a preference for the strategy, Stag , that most often provided the highest payoff (Parrish et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of rhesus monkeys (Macaca mulatta) was more similar to humans than capuchins, especially when no information about the current choice of the partner was available 31 . Interestingly, in a computerized Stag Hunt game, humans adapted more closely than macaques to a simulated partner's stag choice probability, showing that different species might employ distinct but overall fairly successful strategies to maximize reward in a dyadic context 32 .…”
Section: Introductionmentioning
confidence: 99%